A multi-assay assessment of insecticide resistance in Culex pipiens (Diptera: Culicidae) informs a decision-making framework - Kristina Lopez; Patrick Irwin; Daniel Bartlett; Christopher Kukla; Susan Paskewitz; Lyric Bartholomay (PLoS ONE, 2025)
Insecticide resistance (IR) is an increasing problem globally, making control of vector-borne diseases more difficult. Reduced susceptibility to permethrin in Culex pipiens, an important vector for West Nile virus, has been reported across the US based on a standardized laboratory method: the CDC bottle bioassay. This bioassay uses a rapid phenotypic outcome to reveal evidence for IR, but how this translates to the effectiveness of formulated products used in an operational setting is unclear. Therefore, other methods for IR monitoring are recommended to quantify IR or evaluate formulated products against field populations in real-world conditions. To compare some of the available methods, we collected populations of Cx. pipiens from six sites in the Northwest Mosquito Abatement District (Cook Co., Illinois), and used a susceptible laboratory strain of Cx. pipiens as a control, to test for IR to pyrethroids using CDC bottle bioassays, caged field trials, and topical applications. CDC bottle bioassays suggested that Cx. pipiens from this area exhibit IR to both etofenprox and Sumithrin®. Caged field trials with ultra-low volume Anvil® 10 + 10 (Sumithrin®) demonstrated resistance to the product and underscored the need for inclusion of a susceptible control to differentiate IR from inadequate product distribution. Topical applications revealed low to high levels of resistance to synergized and unsynergized pyrethroids (etofenprox, Sumithrin®, and deltamethrin) in all field populations. Based on these data, we provide a new decision-making tree for mosquito control professionals which will guide selection of the most optimal assay for IR surveillance based on their goals, needs, and resources.